Variations of Malangbong-Garut Ladu Product - Rumayar, Christian H; Raissa, . (Universitas Pendidikan Indonesia, 2020)
This study aims to make a variety of Ladu product mixed with roasted peanuts and cashew as additional nutritionns in the product. This research is conducted due to the fact that Ladu is only familiar for local community (Garut resident) and not well known by wider community. Morover,Â Laduâ€™s flavor, shape and, variety are still made in original ones and not yet developed in different variations. By conducting this research, it is expected that Ladu as a traditional food can be an interesting food product for wider community. The method used in this study is a qualitative method because it applied experimental methods.